To fan the fire: Presentation of the special issue “Black and Peripheral Poetics in the Latin America context” - 1 - Gomes Monteiro, Altemar; Feliciano da Silva, Anderson (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2025)
.